Rahasia Sukses Menuntut Ilmu Pengetahuan (Studi Analisa Pemikiran Imam Ali Karamallahu Wajhahu). - Hikmatuloh, Hikmatuloh (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2022)
Imam Ali Karamallahu Wajhahu, is the cousin of the Prophet Muhammad as well as his son-in-law and one of the 10 (ten) companions of the Prophet who are guaranteed to enter heaven. Among the privileges of Imam Ali Karramallahu Wajhahu is the nickname "the gate of knowledge. This was proven when 10 Khawarij asked the same question, but the answers were different. According to Imam Ali Karamallahu Wajhahau, the secret to success in studying knowledge is 6 (six) conditions. that is ; intelligent, earnest, patient, have provisions (money), have a teacher who guides, and a long time. Judging from its type, this research uses literature research (Library research), or literature review that aims to obtain objective and scientific values. This research uses naturalism or natural paradigm. This research does occur naturally, in normal situations that are not manipulated by circumstances and conditions. The research approach used in this research is qualitative. The use of qualitative methods is done because this method is easier to adjust when dealing with multiple realities, besides that this method also presents directly the nature of the relationship between researchers and informants